The Performance Assessment of a Semisubmersible Platform Subjected to Wind and Waves by a CFD/6-DOF Approach - Hongbo Zhu; Dai Zhou; Zhaolong Han; Jin Ma; Yan Bao; Shixiao Fu (Shock and Vibration)
The semisubmersible platform is one of the most important equipment for the exploitation of deep-sea oil and gas. And its survival and operational capacities depend on the towing and motion performances. The present work investigates the properties of different platform component designs based on their towing and motion performances under wind and waves by using an integrated computational fluid dynamics (CFD) method. The joint application of RANS and a VOF/6-DOF solver compiled in a new Fluent UDF Library is adopted for the main calculation. Numerical simulations and results demonstrate that the VOF/6-DOF solver is accurate and stable, which could achieve the same functions as the previous OpenFOAM scheme. In order to acquire a better towing performance, different shapes are suggested for the pontoon end shape, the column cross section, and the brace longitudinal section, respectively. As to the motion response, among all the three design selections, the column cross section has the greatest influence on the whole platform. The simulation results reveal that circle section increases the roll and pitch response and reduces the heave response, to which the square section is adverse.